Effect of Gamma Irradiation on Depolymerization and Property Changes of Gum Tragacanth - Boontiwa Ninchan; Parimitta Chauywongyart; Teerawat Utapong; Nuatawan Thamrongsiripak (International Journal of Biomaterials)
High-energy nonthermal processes (irradiation) are an interesting technique for depolymerization. Gum tragacanth (GT) is a heteropolysaccharide composed of various sugars that are beneficial in the food and pharmaceutical industries. This study investigated the effects of different gamma irradiation doses (2.5, 5, 10, 20, 100, 500, 1,000, and 2000 kGy) on GT properties, considering both structural and physicochemical changes. The results confirmed that gamma irradiation influenced depolymerization with increases in monosaccharides (L-arabinose, D-galactose, D-glucose, D-xylose, L-fucose, L-rhamnose) and the percentage of degradation. Fourier transform infrared (FTIR) spectroscopy analysis indicated that structural changes occurred, with more free O-H and C-O bonding, including the carboxylic group (COOH) in the degraded molecules after irradiation. The changes in physicochemical properties were lower viscosity and a color change under gamma irradiation. The property changes in the GT were clearly related to an increased dose of gamma rays. In summary, there was comprehensive GT degradation following exposure using different increasing doses of gamma radiation, with some concomitant property changes in the GT.